Kalman filter implementation in matlab environment - Yeo, Kelvin. (2013)
Kalman filter (KF) is one of the famous recursive algorithm developed in the twentieth century to solve the problem of discrete-data linear filtering. Since it was first introduced in the paper written by R.E. Kalman, it has been widely researched on and implemented in various fields such as automation, navigation and even economics. The capabilities of the algorithm is not limited to just producing estimation from a noisy source, it is also able to estimate the past and future state given the current state. [1] This method comprises of 2 parts in the iteration, namely the prediction step and the update step.